STUDY ON CONVERSION OF SUBSIDIZED KEROSENE AS FUEL TO COAL AT TOBACCO DRYING INDUSTRY IN NUSA TENGGARA BARAT (NTB) PROVINCE - IJANG SUHERMAN (Puslitbang tekMIRA, 2009)
In the last two years, a regulation on conversion of kerosene as subsidized fuel to alternative fuel for tobacco drying industry in NTB Province was issued. Coal as alternative fuel has a significant role in the conversion process. The process has been smoothly implemented due to advantageous condition like technical and economic aspects, supplier, port, and transporting structure and infrastructure. For 2007, 9,450 tons of coal has been consumed equal to conversion of 4,725 kilolitres (kl) of kerosene, making up the saved subsidy of IDR 16.112 billion. For 2011, coal consumption is predicted to reach 48,420 tons or convert 24,210 kl kerosene with the saved subsidy amount of IDR 82.556 billion. The amount can be doubled, if the conver- sion uses coal 100%. From the economic analysis, the efficiency of using coal as fuel is 28.4%, which equals to IDR 980 per kg. By using liquid petroleum gas (LPG), the cost for fuel will increase by 32.62% or equals to IDR 1,126 per kg.